Sydney Caquelin: capstone - Caquelin, Sydney, artist (Colorado State University. Libraries, 2026)
The artist's statement: I use art as a positive outlet for creativity and taking time to enjoy the process. I am drawn to both graphic design and other traditional forms of art and often move between digital and physical mediums. I enjoy drawing, painting, and exploring other materials. While sometimes they do remain separate, there are times when I combine them or let them influence one another. Within my graphic design process, I tend to focus on refinement and iteration. I work on the same idea multiple times, altering different versions and exhausting it to see all the potential with it. This process helps me identify the strongest areas of an idea and make more intentional decisions that are best for the project. Also, I enjoy adding subtle details or hidden elements into my designs. They are not always immediately obvious, but they add layers of meaning that create an intentional and thoughtful design. Although working physically, my process is more expressive. I lean into form and texture over accuracy or realism. I work with acrylic paints, alcohol markers, graphite, and pens. I enjoy the mark making process across all mediums and using color on the surface to create a work of art. For the most part, my work comes together in an impressionistic way. I try to branch out into other styles to better understand a medium and subject. Across each field, I value the patience and time it takes to create something. Whether I use software for a design or build up layers of paint, I enjoy taking the time to make decisions about a piece. I also want to continue to grow and improve my skills. While I have my favorite mediums and styles, I explore other areas to expand my knowledge. Whether it is digitally or physically, I strive to be a more well-rounded artist.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design